Newton's cradle-like allosteric mechanism explains regulatory RsmE RNA binding - Finol, Esteban; Damberger, Fred F; Krepl, Miroslav; Flügel, Timo; Dietrich, Priscilla; Michaels, Thomas C T; Vögeli, Beat; Šponer, Jiří; Allain, Frédéric H-T (Research square, 2025)
In the bacterial Csr/Rsm system, non-coding RNAs activate mRNA translation by removing homodimeric Csr/Rsm proteins from the ribosome-binding sites of mRNAs. In Pseudomonas protegens, each RsmZ ncRNA sequesters up to five RsmE dimers sequentially and specifically within a narrow affinity range, functioning as a 'protein sponge'. Although the RsmE binding cascade is cooperative, binding of the highest affinity stem-loop RNA in RsmZ (SL2) reduces RNA binding affinity at the second site by 10- to 30-fold. This unusual negative cooperativity may facilitate RsmE release from tightly bound mRNA for handover to the non-coding RNA, yet the underlying mechanisms remain unclear. Using Isothermal Titration Calorimetry, NMR spectroscopy and Molecular Dynamic simulations, we show that the initial binding event increases conformational entropy at the empty site, partially unfolding the C-terminal helix. Moreover, we reveal an allosteric mechanism coupling RNA binding at the first site to conformational changes at the second site, explaining the reduced affinity of the second binding event. The anti-parallel β-sheets in the RsmE dimer facilitate communication between sites, with H-bond constriction at the bound site and relaxation at the empty site, resembling a Newton's cradle.